TINJAUAN SYARIAH MULTI LEVEL MARKETING - Tanjung, Hendri (MIZAN: JOURNAL OF ISLAMIC LAW, 2013)
Multi Level Marketing is a method or technique of multi-level marketing and use direct selling approach. The uniqueness of this system lies in the distribution of its products will not be found in shops, supermarkets and stalls. Products obtained through direct distributors that are mainly individuals. But in the run still leaves some problems, especially in view of sharia, such as how the halal products, how the validity of the agreement, if it is appropriate reward with his work, how the ethical position of MLM, how the rule of law, as well as how to modify them in accordance with sharia.